2013
DOI: 10.1038/nn.3401
|View full text |Cite
|
Sign up to set email alerts
|

Melanin-concentrating hormone regulates beat frequency of ependymal cilia and ventricular volume

Abstract: Ependymal cell cilia help move cerebrospinal fluid through the cerebral ventricles, but the regulation of their beat frequency remains unclear. Using in vitro, high-speed video microscopy and in vivo magnetic resonance imaging in mice, we found that the metabolic peptide melanin-concentrating hormone (MCH) positively controlled cilia beat frequency, specifically in the ventral third ventricle, whereas a lack of MCH receptor provoked a ventricular size increase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
66
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 19 publications
12
66
0
2
Order By: Relevance
“…When applied to real data, the MLE method was successfully used to determine the CBF of ependymal cells boarding the mouse third ventricle in brain slices [2]. In this study, we have shown that the CBF varies from slice to slice between 2 and 16 Hz with an average of 11.18 ± 0.72 Hz (N = 55 slices in 14 mice) and that it is positively modulated by the neurotransmitter serotonin, by ATP and by the hypothalamic peptide melanin-concentrating hormone (MCH).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When applied to real data, the MLE method was successfully used to determine the CBF of ependymal cells boarding the mouse third ventricle in brain slices [2]. In this study, we have shown that the CBF varies from slice to slice between 2 and 16 Hz with an average of 11.18 ± 0.72 Hz (N = 55 slices in 14 mice) and that it is positively modulated by the neurotransmitter serotonin, by ATP and by the hypothalamic peptide melanin-concentrating hormone (MCH).…”
Section: Resultsmentioning
confidence: 99%
“…7e illustrates that it is possible to record higher CBFs. It shows the effects on CBFs recorded at 34 • C (thus with a faster baseline CBF) of increasing concentrations of an orexigenic hypothalamic peptide known to be released during fasting, melanin-concentrating hormone (MCH), which has previously been shown to modulate the CBFs in the third ventricle [2].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropeptides regulate ciliary beating and influence larval swimming behavior in marine annelids (Conzelmann et al, 2011) and melanin-concentrating hormone regulates ciliary beat frequency in the ependymal cells that move cerebrospinal fluid in the ventricles (Conductier et al, 2013). In addition, the G-proteincoupled receptors for neuropeptide Y, somatostatin and kisspeptin localize to neuronal cilia (Loktev and Jackson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, our data revealed a dynamic control of MCH neurons on spontaneous CBF of MCH-R1-expressing ependymal cells and on cerebrospinal fluid flow in brain ventricles. 40,41 MCH-R2 STRUCTURE AND SIGNALLING The second MCH receptor, named here MCH-R2, was identified in the human genome by use of in silico data mining, and its complementary DNA was subsequently isolated from human brain complementary DNA libraries. 18--19 In contrast to the MCH-R1 gene, which is intronless in its coding region, the MCH-R2 gene encompasses five coding and one noncoding exon and may produce receptor variants by alternative splicing that would lead to a truncated version of MCH-R2.…”
Section: Mch-r1 Structure and Signallingmentioning
confidence: 99%